2008
DOI: 10.1161/hypertensionaha.107.102715
|View full text |Cite
|
Sign up to set email alerts
|

Positron-Emission Tomography Imaging of the Angiotensin II Subtype 1 Receptor in Swine Renal Artery Stenosis

Abstract: Abstract-The angiotensin II subtype 1 receptor (AT 1 R) has been linked to the development and progression of renovascular hypertension. In this study we applied a pig model of renovascular hypertension to investigate the AT 1 R in vivo with positron-emission tomography (PET) and in vitro with quantitative autoradiography. AT 1 R PET measurements were performed with the radioligand [ 11 C]KR31173 in 11 control pigs and in 13 pigs with hemodynamically significant renal artery stenosis; 4 were treated with lisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 48 publications
3
27
0
Order By: Relevance
“…1 These images were consistent with Ͼ70% reductions in intrarenal perfusion in the kidneys with renal artery stenosis compared with contralateral kidneys.…”
Section: Intrarenal Perfusion and Angiotensin II Levels Regulate In Vsupporting
confidence: 70%
See 2 more Smart Citations
“…1 These images were consistent with Ͼ70% reductions in intrarenal perfusion in the kidneys with renal artery stenosis compared with contralateral kidneys.…”
Section: Intrarenal Perfusion and Angiotensin II Levels Regulate In Vsupporting
confidence: 70%
“…1 In this study, AT 1 11 C]KR31173 levels were clearly observed at 2 minutes, which were followed by marked increases in [ 11 C]KR31173 accumulation in the kidneys with stenosis at 30 minutes after injection of the radioligand. By contrast, most injected […”
Section: Intrarenal Perfusion and Angiotensin II Levels Regulate In Vsupporting
confidence: 51%
See 1 more Smart Citation
“…Renovascular hypertension is the most common type of secondary hypertension that occurs in 2 to 4 million people in the United States [22]. Especially, the renin angiotensin system plays a major role in the regulation of blood pressure and in the pathogenesis of hypertension [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…Currently losartan is on the market as the first AII receptor antagonist that was launched as a novel antihypertensive agent since proven to be orally active in animals [9][10][11] and humans [12][13][14]. Recently, the application of AII receptor antagonists has expanded to ongoing trials for noninvasive diagnostics as in positron emission tomography imaging [15][16][17] …”
Section: Introductionmentioning
confidence: 99%